Exploration of crop germplasm resources knowledge mining in Chinese ancient books: a route toward sustainable agriculture - Zhao, Wenjuan; Zhu, Suoling; Cao, Yuan (Frontiers in Sustainable Food Systems, 2025)
Crop germplasm resources, also known as genetic resources, include local varieties, bred varieties, wild resources and special genetic materials. In China, a large number of local varieties and wild resources have been recorded in ancient books. In this paper, Chinese ancient local chronicles, a unique kind of Chinese ancient books, is taken as an example to discover the knowledge of crop germplasm resources and explore their practical applications. Using the local chronicles of Jiangsu Province, China (1251–1947) as the data source, we constructed a spatio-temporal ontology of rice species according to the writing paradigm of descriptive texts on rice, intelligently extracted the features of rice with entity word lists and rule templates, and compared them with existing rice germplasm resources to analyze the similarities and differences. It is found that the descriptive texts on rice in Chinese ancient local chronicles not only contain the knowledge about the morphological characteristics of rice germplasm resources gained by field observation, but also involve the experience about the inherent attributes summarized by hands-on practice, such as the function, quality, phenology, customs, etc. It is a complement to the current collection and utilization of germplasm resources. Furthermore, some of the excellent varieties discovered still possess good trait stability after nearly a century of natural evolution and artificial selection, which provides a solid germplasm base for sustainable agricultural development. This study provides reference for the genetic breeding and insights for the knowledge discovery in the field of the history of agricultural science, and injects new vitality into the sustainable development of agriculture.